1985
DOI: 10.1007/bf00543327
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state concentration of cotinine as a measure of nicotine-intake by smokers

Abstract: Measurement of plasma cotinine, the major metabolite of nicotine, is usually done to determine nicotine-intake in smokers. Cotinine is used instead of nicotine because it has a much longer half-life than the mother substance and its plasma concentrations are therefore less dependent on the exact times of blood sampling. However, the linearity of the relationship between nicotine-intake and cotinine level in plasma has never been proven. Therefore cotinine was measured in 6 healthy volunteers infused over 4 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Thus, cotinine has been recommended as a parameter for nicotine consumption or abstinence (e. g. Benowitz et al 1983) and it has been demonstrated that plasma concentrations of cotinine are related to nicotine intake in man (Galeazzi et al 1985). Cotinine, which is a long-lived metabolite of nicotine, may enter secondary metabolic pathways leading to cotinine-N-oxide, norcotinine and trans-3'-hydroxycotinine (Wada et al 1961;Bowman and McKennis 1962;Dagne and Castagnoli 1972;Hibbert and Gorrod 1985).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, cotinine has been recommended as a parameter for nicotine consumption or abstinence (e. g. Benowitz et al 1983) and it has been demonstrated that plasma concentrations of cotinine are related to nicotine intake in man (Galeazzi et al 1985). Cotinine, which is a long-lived metabolite of nicotine, may enter secondary metabolic pathways leading to cotinine-N-oxide, norcotinine and trans-3'-hydroxycotinine (Wada et al 1961;Bowman and McKennis 1962;Dagne and Castagnoli 1972;Hibbert and Gorrod 1985).…”
Section: Discussionmentioning
confidence: 97%
“…Usually, cotinine is present in the plasma of smokers in concentrations exceeding those of nicotine and it remains there longer than nicotine after cessation of smoking (Benowitz et al 1983;Galeazzi et al 1985). Thus, cotinine has been recommended as a parameter for nicotine consumption or abstinence (e. g. Benowitz et al 1983) and it has been demonstrated that plasma concentrations of cotinine are related to nicotine intake in man (Galeazzi et al 1985).…”
Section: Discussionmentioning
confidence: 98%
“…To quantify ETS exposure, we measured plasma cotinine, a good indicator of exposure to cigarette smoke (17). Because lifestyle factors can also influence oxidative DNA damage, we also investigated the effect of physical activity, body mass index, alcohol, and tea and coffee consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, cotinine is present in the plasma of smokers in concentrations exceeding those of nicotine and it remains there longer than nicotine after cessation of smoking [2,12]. It has been demonstrated that the plasma concentrations of cotinine are closely related to nicotine intake [12] and that the elimination kinetics of cotinine from plasma are directly proportional to the corresponding values in saliva [6,21]. Therefore, cotinine has been recommended as a biomarker for nicotine intake [2,6,21,33], although there are some limitations to this approach [19].…”
Section: Discussionmentioning
confidence: 99%